The new concepts of measurement error theory. (April 2016) - Ye, Xiaoming; Xiao, Xuebin; Shi, Junbo; Ling, Mo
Abstract: In current measurement theory, there are various logical and philosophical troubles, and the evaluation concepts of measurement error are various and inconsistent among different schools. This paper throws away the shackle of the current measurement theories and concepts, and re-discusses basic measurement concepts. By proving a new measurement error theory that any error is a bias and follows random distribution, this paper points out the misunderstanding of traditional measurement theory, subverts the traditional error category theory, gives out a new interpretation of measurement uncertainty concept, proposes abolishing the concept system of precision, trueness, and accuracy, and thereby achieves the united measurement concept system across all the disciplines, including geodesy, geomatics, metrology, instrumentation, and so on.